Dual Viscosity Mixture Vehicle for Intratympanic Dexamethasone Delivery Can Block Ototoxic Hearing Loss - Li, Hui; Suh, Myung-Whan; Oh, Seung Ha (Frontiers in Pharmacology, 2021)
Clinically there is no effective method to prevent drug induced hearing loss in patients undergoing chemotherapy and anti-tuberculosis therapy. In this study, we developed an intratympanic (IT) local drug delivery vehicle featuring hyaluronic acid-based dual viscosity mixture encapsulation of dexamethasone (D), named dual-vehicle+D, and assessed its protective effect in ototoxic hearing loss. We assessed the residence time, biocompatibility, and treatment outcome of the novel vehicle compared with the current standard of care vehicle (saline) and control conditions. The hearing threshold and hair cell count were significantly better in the dual-vehicle+D group compared to the other two groups. The final hearing benefit in the dual-vehicle group was approximately 25–35 dB, which is significant from a clinical point of view. Morphologic evaluation of the cochlear hair cells also supported this finding. Due to the high viscosity and adhesive property of the vehicle, the residence time of the vehicle was 49 days in the dual-vehicle+D group, whereas it was less than 24 hours in the saline+D group. There was no sign of inflammation or infection in all the animals. From this study we were able to confirm that dual viscosity mixture vehicle for IT D delivery can effectively block ototoxic hearing loss.